Objects of amplified context: an interview with artist-teacher Pepón Osorio. Issue 3 (19th September 2011) - Corner, John; Richardson, Kay; Parry, Katy
This article seeks to contribute to the emerging literature on the mediation of politics in the wider sphere of civic and popular culture. By focusing on one particular country, the United Kingdom, and on a specific audit period, February 2010, we present some preliminary findings from a larger project assessing contemporary mediations of politics and the political across a diverse range of genres within print, broadcast and online media. Our findings are derived from three complementary studies, one focusing on the variety of generic forms through which the story of 'MPs expenses' was mediated; one focusing on a reality-style series, Tower Block of Commons, and the range of ways that it sought to engage the political imagination of its audience; and a final study addressing the place of emotions in political life. Substantively, the findings point towards a desire for a new moral order for British politics, including a new kind of politician. Theoretically, the article validates the proposition that there is much more to political mediation than the dominant focus on political journalism can satisfactorily encompass.